PKM PENGERINGAN KAYU UNTUK PENINGKATAN PRODUKSI PADA PENGRAJIN KAYU LOKAL DI BANJARBARU, KALIMANTAN SELATAN - Wiwin Tyas Istikowati; Sunardi Sunardi (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2019)
One of the problems of traditional wood industry in Banjarbaru, South Kalimantan is wood drying process. Drying process that safe, fast, and effective is looking for to improve the quality of the product. The aim of this program is to train the wood traditional businessman to dry the wood using green house kiln dry. This kiln using sun radiation to dry the wood. Good position and design of kiln and the right process of drying are the key of the successfully of wood drying. The time of drying process and wood defects during drying process can be reduced. Using green house kiln dry, the time of drying can be reduced from 2 moths to be 1 month and the defects do not appear clearly.